Effect of micronised oat bran by ultrafine grinding on dietary fibre, texture and rheological characteristic of soft cheese. (18th August 2019) - Xue, Xiuheng; Wang, Juhua; Li, Shaohua; Zhang, Xiuxiu; Dong, Jinhua; Gui, Lin; Chang, Qianqian
Summary: The purpose of this research was to study the effect of micronised oat bran on dietary fibre, textural and rheological of soft cheese. The soft cheese was processed by using the different particle size oat bran as fibre supplement, and its dietary fibre content, rheological and textural properties were determined. The results show that the micronised oat bran with 5–30 μm particle size was prepared by ultrafine grinding and passed through 60–400 mesh sieves. The soluble dietary fibre content in micronised oat bran soft cheeses was higher than that of the control (untreated oat bran soft cheeses; P  < 0.05), with a maximum of 2.65 g per 100 g cheeses when oat bran was ultrafine crushed and passed through 300 mesh sieves, while the content of insoluble dietary fibre was lower than that of the control ( P  < 0.05). The micronised oat bran soft cheese in fermentation is a typical non‐newtonian fluid. G′, G″ and apparent viscosity of soft cheeses were increased with the reduction of oat bran particle size. The chewiness and springiness of micronised soft cheeses were increased with the reduction of oat bran particle size, and were higher than that of the control ( P  < 0.05). The hardness and cohesiveness of micronised soft cheese were decreased with the reduction of oat bran particle size, the hardness was lower, but the cohesiveness of micronised soft cheese was higher than that of the control ( P  < 0.05). The 1% micronised oat bran can obtain better processing characteristics and overall acceptability for cheese products. Abstract : The soft cheese was processed by using the different particle size oat bran after ultrafine grinding as fibre supplement and the effect of micronised oat bran on dietary fibre, textural and rheological of soft cheese were evaluated. The content of soluble dietary fibre in prepared soft cheese was increased with the reduction of oat bran particle size from passed through 60 to 400 mesh sieve. The micronised oat bran could obtain better rheological properties, texture and sensory property for soft cheese.